First‐Principle Results for the Radial Pair Distribution Function in Strongly Coupled One‐Component Plasmas. Issue 2 (27th November 2014) - Ott, T.; Bonitz, M.
Abstract: The radial pair distribution function (RPDF) is the most simple way to characterize the structure of a system. In this work, we provide a comprehensive overview of the dependence of the RPDF on the coupling parameter and screening length in Coulomb and Yukawa One‐Component plasmas. These data allows for a precise assessment of the coupling strength of experiments and simulations via a structural measurement and give a benchmark for analytical models. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)